2012
DOI: 10.1128/jvi.02662-10
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Chaperone Hsc70 Is Specifically Recruited to Reovirus Viral Factories Independently of Its Chaperone Function

Abstract: Mammalian orthoreoviruses replicate and assemble in the cytosol of infected cells. A viral nonstructural protein, NS, forms large inclusion-like structures called viral factories (VFs) in which assembling viral particles can be identified. Here we examined the localization of the cellular chaperone Hsc70 and found that it colocalizes with VFs in infected cells and also with viral factory-like structures (VFLs) formed by ectopically expressed NS. Small interfering RNA (siRNA)-mediated knockdown of Hsc70 did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Hspa1L and Hspa2 are sperm proteins which are important for sperm functions [45], [46]. Hspa8 is important in viral assembly in cells, independently of its chaperone function [47]. Some heat shock proteins have functions in gonad development, for example, Hsp10 and Hspa2 [21], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hspa1L and Hspa2 are sperm proteins which are important for sperm functions [45], [46]. Hspa8 is important in viral assembly in cells, independently of its chaperone function [47]. Some heat shock proteins have functions in gonad development, for example, Hsp10 and Hspa2 [21], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies using electron microscopy identified inclusion-associated cytoskeletal elements, including coated microtubules and thick, kinked fibrils interspersed among viral particles (13,16). Known cellular proteins recruited to reovirus inclusions include chaperone Hsc70 (20) and clathrin (19). The roles played by these proteins in inclusion formation and function await further investigation.…”
Section: Figmentioning
confidence: 99%
“…Among the major Hsp70 proteins expressed at high levels in a wide range of tissues, stress-inducible heat shock protein 70 (Hsp72) and constitutively expressed heat shock cognate protein 70 (Hsc70) are present in the cytoplasm and nucleus, while glucose-regulated protein 78 (GRP78) and GRP75 are localized in the lumen of the endoplasmic reticulum (ER) and the mitochondrial matrix, respectively. During virus infections, Hsp70 family proteins are frequently mobilized to the viral replication sites and play roles in all steps of the life cycles of many DNA and RNA viruses (4,(15)(16)(17). In the case of negative-strand RNA viruses, Hsp70 has been found to have both positive and negative regulatory effects on viral propagation.…”
mentioning
confidence: 99%